Peningkatan Kemampuan Penyesuaian Diri Anak Usia Dini Melalui Bermain Peran Mikro - Suci Midsyahri Azizah; Dian Maharani (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2019)
School environment is a new environment after the family environment for some students in early education, namely in Early Childhood Education. By playing in groups children will also learn to adjust their behavior with other children, learn to master themselves and their ego, learn to hold back, be able to regulate emotions, and learn to share with others. In terms of emotions, unspoken desires are increasingly formed when children play imagination and sociodrama / role playing. To be able to make adjustments, early childhood experiences are introduced to what is called socialization or interaction with other people such as peers, other adults, and so on. This research uses the Action research method with 2 implementation cycles which in learning uses the application of role playing methods. Based on the results of data analysis obtained from the conclusions that: (1) Micro role playing method has been planned and then carried out in accordance with the steps that have been formulated, role playing can also be purely carried out by the students themselves. Which in the process contains a stimulus to achieve the expected goals. (2) The application of the micro role playing method can improve students' self-adjustment abilities with the environment in the Ponorogo Khairiah Jimbe Jenangan Play Group. Keywords: Role Playing, Self-Adjustment, Early Childhood Education